2009
DOI: 10.1177/1099800409331892
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Stress-Related Substances in Saliva and Immune Substances in Breast Milk in Puerperae

Abstract: The only association found in our study was between the salivary and breast milk SIgA. The lack of association among SIgA and cortisol may be related to a variety of factors such as production site, diurnal rhythms, and the interval between stress stimulation in mothers and the response of the biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…Free TRP binding to albumin can be influenced by many factors such as hormones, nutrition, pregnancy, drugs and NEFA ( 5 , 35 ) . In this preliminary study, we chose to use hind milk primarily to avoid interfering with infant feeding ( 34 , 36 ) . Hind milk has a much higher fat content in comparison with aqueous-rich foremilk ( 37 39 ) , and, consequently, higher levels of NEFA which could have an effect on albumin-bound TRP.…”
Section: Discussionmentioning
confidence: 99%
“…Free TRP binding to albumin can be influenced by many factors such as hormones, nutrition, pregnancy, drugs and NEFA ( 5 , 35 ) . In this preliminary study, we chose to use hind milk primarily to avoid interfering with infant feeding ( 34 , 36 ) . Hind milk has a much higher fat content in comparison with aqueous-rich foremilk ( 37 39 ) , and, consequently, higher levels of NEFA which could have an effect on albumin-bound TRP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested for some time that stress exposure during the perinatal period may affect the quality of milk (Kawano et al, 2009), which is fundamental not only to sustain child growth and development (Butte and King, 2005;Hair et al, 2013), but also to support the normal brain functioning of the child (Horta et al, 2018). Indeed, maternal milk is an important physiological fluid for nutrient transfer and immune signalling, which potentially shapes infant growth at a cognitive, behavioral and motor level.…”
Section: Introductionmentioning
confidence: 99%
“…Self-perceived stress is the cognitive appraisal of physical and environmental stressors and has been associated with increased levels of prenatal and postnatal serum cortisol. [38][39][40][41] Prolonged elevation of maternal serum cortisol levels can influence the infant immune system response and potentially the milk immune components (MICs). 42 Groer et al 42,43 reported higher self-perceived stress was associated with higher serum cortisol (r = 0.25, p = 0.040) as well as greater levels of milk secretory immunoglobulin A (SIgA).…”
Section: Introductionmentioning
confidence: 99%